عوامل التغير الدلالي في اللغة العربية بين القديم والحديث The Causes of Semantic Change in the Arabic Language: Past and Present - الحاج عبد الله (Mohd. Bakhir Bin Abdullah) محمد باخير (At-Tajdid - Intellectual Refereed Journal, 2011)
مستخلص البحث دلالة الألفاظ وما يعتريها من تغير وتطور في دلالاتها من أهم قضايا الدراسات اللغوية الحديثة، بل إنها أصبحت فرعًا علميًّا بذاته في عصرنا. وتنبع الدلالة أهمية الدلالة والتغير الدلالة من أثرهما الكبير في مساقات التعبير عن المواقف والأفكار وفي كيفيات التواصل والتفاهم بين الناس، مما يخضع لاعتبارات مختلقة بحيث لا يحصل ذلك التواصل والتفاهم على أفضل الوجوه من دون أخذها بعين الاعتبار. وقد اجتهد العلماء القدامى والمحدثون في رصد العوامل المختلفة التي تؤثر في دلالات الألفاظ إفرادًا وتركيبًا، مقالاً ومقامًا، مما لا بد لدارس اللغة أو الساعي إلى تعلمها من إدراكه والتفطن إليه. وتتأكد أهمية هذه الاعتبارات بخصوص للغة العربية التي تحتل مكانة خاصة بالنسبة للإنسان المسلم تتجاوز مجرد كونها وسيلة للتواصل بين مجموعات معينة من البشر إلى كونها حاملاً للوحي القرآني وخطاب الخالق سبحانه إلى العباد. في ضوء ذلك كله يسعى هذا البحث إلى النظر في عوامل التغير الدلالي في هذه اللغة الكريمة ورصدها وتحليلها بالاستفادة من إسهامات علماء العربية الأقدمين وإسهامات الباحثين اللغويين في العصر الحديث، آملاً في أن يكون ذلك عونًا لمن يرغب في تعليمها وتعلمها على بلوغ غايته. الكلمات الأساسية: اللغة العربية، الألفاظ، الدلالة، التغير الدلالي، عوامل التغير الدلالي. Abstract The significance of words and the semantic change affecting them are among the important issues in modern linguistic studies. Indeed, this has become an independent branch of scientific study in our time. The importance semantics and semantic change stems from their influence on the modes of expression of positions and ideas and the ways of communication and understanding among human beings. This is subject to different considerations that have to be taken into account if such communication and understanding are to take place in the best possible manner. Scholars both in the past and in the modern era have endeavoured to identify the different factors of semantic change affecting words as such and in composition as well as in textual and situational context. These factors are such that no teacher or learner of language can avail not knowing and being aware of. The importance of these considerations is further emphasized in the case of the Arabic language whose standing and position transcends its being a mere means of communication among certain people to be the vehicle of the Qur’anic revelation and of God’s Word to mankind. In light of the above, this article attempts to look into the factors of semantic change in Arabic by identifying and analyzing them based on the contributions of classical scholars of Arabic and the studies of modern linguists. It is hoped that is effort will be of help for both teachers and learners of the Arabic language to achieve their goals. Key terms: Arabic language, words, significance, semantics, semantic change, factors of semantic change. Abstrak Perubahan makna pada kata-kata dan perubahan semantik yang mempengaruhinya adalah antara isu-isu penting dalam kajian linguistik moden. Memang, hal ini telah menjadi cabang kajian ilmiah tersendiri di zaman sekarang. Pentingnya semantik dan perubahannya berasal dari pengaruhnya pada cara berekspresi kedudukan dan idea-idea dan cara komunikasi dan pengertian di antara manusia. Hal ini tertakluk pada pertimbangan dalam ekspresi sikap, idea-idea dan cara komunikasi dan pemahaman antara setiap orang. Cendekiawan baik di masa lalu dan di era moden telah berusaha untuk mengenal pasti faktor yang berbeza yang mempengaruhi perubahan semantik kata-kata seperti itu dan dalam komposisi serta dalam konteks perkataan dan situasional. Faktor-faktor ini sedemikian rupa sehingga tidak ada guru atau pelajar bahasa yang tidak tahu dan menyedari. Pentingnya kajian ini juga disebabkan Bahasa Arab telah menduduki tempat khusus bagi orang muslim dari sekadar menjadi sarana komunikasi antara sesama, tetapi juga untuk menjadi sarana memahami wahyu Al-Qur’an dan surat dari Tuhan kepada manusia. Maka tulisan ini mencuba untuk melihat ke dalam faktor-faktor perubahan semantik dalam bahasa Arab dengan mengenalpasti dan menganalisis mereka berdasarkan sumbangan dari ulama klasik Arab dan kajian dari ahli bahasa moden. Diharapkan bahawa usaha ini akan membantu para pengajar dan pelajar bahasa Arab untuk mencapai tujuan mereka. Kata kunci: Bahasa Arab, kata-kata, makna, semantik, perubahan semantik, faktor perubahan semantik.